2021
DOI: 10.1177/11206721211036289
|View full text |Cite
|
Sign up to set email alerts
|

Intraretinal, sub-retinal, and sub-retinal pigmented epithelium fluid in non-exudative age-related macular degeneration: follow-up with OCT imaging

Abstract: Background/objectives: To evaluate the presence and evolution of fluid in non-exudative age-related macular degeneration (AMD) through serial OCT. Subjects/methods: A retrospective analysis of eyes with non-exudative AMD with a minimum of 4 year follow-up was done. Parameters including intraretinal fluid (IRF), subretinal fluid (SRF), and sub-retinal pigment epithelium (RPE) fluid (SRPEF); subfoveal choroidal thickness (SFCT) and type of drusen were evaluated using optical coherence tomography (OCT) scans at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Globally, the presence of fluid is still considered to be a universal OCT biomarker for neovascular activity [37]. However, in daily clinical practice, the possibility of confusion, incorrect documentation, and misinterpretation must be anticipated, particularly as some recent studies have provided insight into the various non-neovascular pathways of exudation in eyes with AMD, suggesting that the presence of fluid is not always an indicator of neovascular activity in AMD [38][39][40]. These pathways include cellular degeneration, retinal pigment epithelium dysfunction, pachychoroid disorders, and vitelliform lesions [27].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the presence of fluid is still considered to be a universal OCT biomarker for neovascular activity [37]. However, in daily clinical practice, the possibility of confusion, incorrect documentation, and misinterpretation must be anticipated, particularly as some recent studies have provided insight into the various non-neovascular pathways of exudation in eyes with AMD, suggesting that the presence of fluid is not always an indicator of neovascular activity in AMD [38][39][40]. These pathways include cellular degeneration, retinal pigment epithelium dysfunction, pachychoroid disorders, and vitelliform lesions [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand that both IRF and SRF can be the result of nonneovascular pathways in the context of AMD. [9][10][11][12][13][14] The presence of IRF and SRF with OCT does not always indicate neovascular activity and can be a sign instead of degenerative mechanisms. Pseudocysts were originally described by Cohen et al 15 and represent a form of IRF overlying the areas of retinal pigment epithelium (RPE) atrophy and cRORA (complete RPE and outer retinal atrophy).…”
Section: Nonneovascular Intraretinal Fluid Associated With Cellular D...mentioning
confidence: 99%
“…However, recent studies have provided insight into the various nonneovascular pathways of exudation in eyes with AMD and indicate that fluid can have a much more complex and nuanced etiology and is not always an indicator of neovascular activity in AMD. [9][10][11][12][13][14] Although some have labelled nonneovascular fluid as a transudate and neovascular fluid as an exudate, 11,13 the mechanisms may be more complicated, and therefore, any form of fluid leakage (neovascular or nonneovascular) is best referred to as exudation. The subsequent sections of this editorial will summarize the various nonneovascular pathways of exudation (examples of exudation include IRF, SRF, and/or vitelliform lesions) in AMD and will provide guidelines for the diagnosis and management of nonneovascular fluid.…”
mentioning
confidence: 99%
“…83 Further studies have confirmed that the presence of subretinal fluid may result in advanced AMD, with both an increased risk of exudative AMD and cRORA/iRORA long term. 84,85 Recognition of this phenomenon is necessary to prevent overtreatment with anti-VEGF injections. 84 Figure 10.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The presence of fluid, including subretinal fluid, without evidence of choroidal neovascular membrane in nonexudative AMD has been described 83 . Further studies have confirmed that the presence of subretinal fluid may result in advanced AMD, with both an increased risk of exudative AMD and cRORA/iRORA long term 84,85 . Recognition of this phenomenon is necessary to prevent overtreatment with anti-VEGF injections 84 …”
Section: Introductionmentioning
confidence: 98%